2007
DOI: 10.1002/ajmg.b.30529
|View full text |Cite
|
Sign up to set email alerts
|

Porcine maternal infanticide as a model for puerperal psychosis

Abstract: Childbirth is a period of substantial rapid biological and psychological change and a wide range of psychotic disorders can occur ranging from mild 'baby blues' to severe episodes of psychotic illnesses. Puerperal psychosis is the most extreme form of postnatal psychosis, occurring in 1 in 1,000 births. In this study, we have used the pig as an animal model for human postnatal psychiatric illness. Our aim was to identify quantitative trait loci (QTL) associated with maternal (infanticide) sow aggression. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 69 publications
5
46
0
1
Order By: Relevance
“…The frequency of occurrence in primiparous sows has been estimated in large surveys of commercial pig farms to be 8% [Knap and Merks, 1987] and 7-12% [ Van der Steen et al, 1988]. General behavior shown in these animals and factors affecting it are discussed in more detail elsewhere [Quilter et al, 2007]. However, porcine maternal behavior seems to be mostly influenced by genetic predisposition and the sows' previous experiences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of occurrence in primiparous sows has been estimated in large surveys of commercial pig farms to be 8% [Knap and Merks, 1987] and 7-12% [ Van der Steen et al, 1988]. General behavior shown in these animals and factors affecting it are discussed in more detail elsewhere [Quilter et al, 2007]. However, porcine maternal behavior seems to be mostly influenced by genetic predisposition and the sows' previous experiences.…”
Section: Introductionmentioning
confidence: 99%
“…It is our hypothesis that pigs can be used as a model for human postnatal illness, particularly puerperal psychosis, as maternal infanticidal aggression in pigs has many features in common [Quilter et al, 2007]. Childbirth in women can be a trigger for a wide range of psychotic disorders ranging from mild ''baby blues'' to severe episodes of psychotic illnesses .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be a sign of a higher genetic predisposition to react to involuntary crushing in some sows, and these sows also benefit from a higher genetic merit for progeny growth (Grandinson et al, 2002). Several QTL related to maternal cannibalism have been observed, with a promising one on the X chromosome (Quilter et al, 2007;Chen et al, 2009). In hens, Xu et al (2010) found three QTL involved in egg incubation behaviour, which was put at a disadvantage by selective breeding; among these QTL one was linked to the DRD1 gene, which encodes a dopamine receptor.…”
Section: Maternal Behaviourmentioning
confidence: 99%
“…In pigs, two studies found QTL located on chromosome X and associated with extreme form of failure of maternal behavior, i.e. sow maternal aggression to their own new born piglets (Quilter et al, 2007;Chen et al, 2009). To our knowledge, the present study is the first GWAS for type traits in beef cattle.…”
Section: Literaturementioning
confidence: 99%